Analysis of Factors Influencing Viu Application User Satisfaction using the End User Computing Satisfaction (EUCS) and DeLone & McLean - Sabrina, Dea Fitri; Indah, Dwi Rosa; Firdaus, Mgs Afriyan; Gumay, Naretha Kawadha Pasema (Sistemasi: Jurnal Sistem Informasi, 2024)
One area of telecommunications technology that is also undergoing development in the context of entertainment is that of video streaming. Viu is a video streaming service that provides a range of premium content free of charge. Nevertheless, the Viu application continues to elicit a range of grievances, with the application’s rating remaining relatively low. It is of great importance to consider user satisfaction with an application. This research employs two methods, namely End User Computing Satisfaction (EUCS) and Delone & McLean, to ascertain the factors influencing user satisfaction with the Viu application. A sample of 244 respondents was obtained for the purposes of this research. The data obtained was analysed using the PLS-SEM technique with the Smart-PLS 4 tool. The final results obtained were that the variables of content, ease of use, timeliness, system quality, and finally information quality have a significant effect on user satisfaction.